Modifying the photobehaviour of guest molecules by inclusion within zeolites. - Corrent, Sonia. (University of Ottawa (Canada), 2000)
This thesis gives a detailed account of photochemical processes that occur upon excitation of guest species included inside zeolite host cavities. The use of zeolites, which contain an internal pore structure, as 'microreactors' that can house a variety of molecules differing in size and shape has a remarkable influence on the outcome of photochemical processes, as well as on the behaviour of the transient species formed. The work presented in the various chapters all have an underlying theme: to acquire an understanding of the photochemical and photophysical processes of guest species encapsulated in a constricted medium, and to use this knowledge in the development of new applications of zeolite materials. Thus, the work presented in this thesis explores many different probe molecules in order to acquire a broad view of how the intrazeolite environment influences the photochemical behaviour of encapsulated species. The topics investigated range from the acid-base properties of coumarin 6 in a series of zeolites, to the effect of spectators on the transient and product formation of encapsulated carbonyl compounds, to the characterization of transparent zeolite films. The relevance of these results in context with other work in the field will also be discussed.
Keywords: Chemistry, Physical.